Strategic analysis of providing corporate sustainability open data - Raphaela Helbig; Sven von Höveling; Andreas Solsbach; Jorge Marx Gómez (Intelligent Systems in Accounting, Finance and Management, 2021)
How companies report their data is undergoing digitization and sustainable transformation. Sustainability is important; therefore, various stakeholders are interested in sustainability information. Companies provide the required information and strive toward the use of information systems to ensure efficient data processing. A possible approach for information provision is open data. This research introduces the idea of corporate sustainability open data (CSOD) as one new mechanism of companies' sustainability self-reporting. Since CSOD is not yet commonly practiced by companies, a strategic analysis of the situation and its possible consequences is conducted with an analysis of strengths, weaknesses, opportunities, and threats. This research provides an overview of companies' sustainable development through open data. Moreover, it identifies drivers, challenges, and reasonable strategies for CSOD adoption. Thus, the research contributes to the establishment of an innovative application of open data in the private sector to support sustainable transformation worldwide.
Keywords: 650; corporate sustainability reporting; data availability; knowledge management; nonfinancial disclosure; open data